Perancangan dan Evaluasi Sistem Transaksi Online Pasar Tradisional Menggunakan Metode Goal Directed Design dan Evaluasi Heuristik - Niati, Ulia; Suratno, Tri; Mauladi, Mauladi (JUSS (Jurnal Sains dan Sistem Informasi), 2019)
Today the development of technology is growing, one of them is a mobile phone that is transformed into a smart phone, as well as a modern market that is developing and easily available and very comfortable physically, this development has involved traditional markets, the government continues to revitalize traditional markets using physical, technological developments are used as a means for developing traditional markets as an effort to facilitate transactions, get information quickly and on target. User interface Of course not separated from the appearance of the user interface Even the user interface is important, because the user interface can provide comfort and convenience for users in accessing any information for which the system can be obtained by the user. The purpose of this research is to create a traditional market online transaction system user interface. Where the research used in this study is the Goal Directed Design method which is a user interface design design method that fits the user's goals and needs. In this study there are five stages of experimental research, modeling, requirements, frameworks, and improvements. As well as the evaluation in this study using heuristic evaluation consisting of 10 principles. The final result of this study is a user interface design design that has been created for further development while the results of this study are 94% in the category of "Very Good".